1985
DOI: 10.1017/s0022172400062884
|View full text |Cite
|
Sign up to set email alerts
|

Acute diarrhoeal disease in children under 7 years of age in a peri-urban slum of Santiago, Chile

Abstract: SUMMARYA group of 168 families who lived in a peri-urban slum in Santiago were surveyed for 9 months. All of them had a child under 7 years of age. Medical activities and data collection were carried out at a Field Station and by means of twice-weekly visits to each home, at which time cases ofdiarrhoea were recorded and investigated. Faecal samples for bacteriological, parasitological and rotavirus studies were obtained during each episode. The characteristics of clinical course, hygienic practices in the fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0
4

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
1
7
0
4
Order By: Relevance
“…Acute infectious diarrhoea is the most frequent cause of morbidity in young children living in developing countries (1). Previous field studies carried out by us in children of various ages, who lived in suburban slums in Santiago showed that they suffer 1 to 2 episodes of diarrhoea per year, depending on the age group and season (2,3). These figures are lower than those obtained in comparable groups in other underdeveloped areas of the world (4)(5)(6) and comparable t o those described for middle class children in the United States (Levine, M., personal communication).…”
mentioning
confidence: 99%
“…Acute infectious diarrhoea is the most frequent cause of morbidity in young children living in developing countries (1). Previous field studies carried out by us in children of various ages, who lived in suburban slums in Santiago showed that they suffer 1 to 2 episodes of diarrhoea per year, depending on the age group and season (2,3). These figures are lower than those obtained in comparable groups in other underdeveloped areas of the world (4)(5)(6) and comparable t o those described for middle class children in the United States (Levine, M., personal communication).…”
mentioning
confidence: 99%
“…From these studies, it is impossible to determine the extent to which being "cleaner,"-that is, having hygienic standards above some undetermined minimal baseline-provides additional protective benefit. 37 maternal knowledge and attitudes malnutrition, age of mother, house appearance, maternal birthplace, mother's general knowledge of diarrhea Stanton, Bangladesh Case control Handwashing, handling of excreta Significantly more maternal handwash-1985 38 and garbage, food handling ing and less disposal of excreta on floor in control subjects Araya, 1985 10 Chile Descriptive Hygienic practices in family Adequate hygienic habits not associcorrelational ated with decreased risk of diarrhea Baltazar,…”
Section: Discussionmentioning
confidence: 99%
“…El sindrome diarreico agudo es causa frecuente de consulta en nuestro medio, especialmcnte en verano. 1 " 3 Si bien la mortalidad por esta entidad ha disminuido notablemente 4 " 7 gracias al tratamiento oportuno y eficaz de sus complicaciones, el numero de hospitalizaclones continua siendo considerable. 8 Esta situation no solo significa costos economicos importantes y danos psicologicos para el nino y sus padres, sino tambien la exposition en el Hospital a riesgos adicionales que estan en ultimo termino entre las causas mas frecuentes de muerte en ninos con diarrea (in-fecci6n intrahospitalaria; diarrea de evolution prolongada; desnutrici6n secundaria).…”
unclassified
“…La correction hidroelectrolitica y acido-base 1 por la via parenteral ha sido fundamental en la disminucion de la mortalidad por diarrea aguda. Sin embargo significa necesariamente hospitalizar al nino deshidratado.…”
unclassified
See 1 more Smart Citation